2013
DOI: 10.1038/cddis.2013.318
|View full text |Cite
|
Sign up to set email alerts
|

A novel extracellular role for tissue transglutaminase in matrix-bound VEGF-mediated angiogenesis

Abstract: The importance of tissue transglutaminase (TG2) in angiogenesis is unclear and contradictory. Here we show that inhibition of extracellular TG2 protein crosslinking or downregulation of TG2 expression leads to inhibition of angiogenesis in cell culture, the aorta ring assay and in vivo models. In a human umbilical vein endothelial cell (HUVEC) co-culture model, inhibition of extracellular TG2 activity can halt the progression of angiogenesis, even when introduced after tubule formation has commenced and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 36 publications
8
57
0
Order By: Relevance
“…It was recently reported that extracellular TGase2 inhibits VEGF-induced angiogenesis by impeding the interaction of VEGF with heparan sulfate proteoglycans and subsequent VEGF receptor-2 signaling independent of its transamidating activity (39). There are, however, contradictory reports on the involvement of extracellular TGase2 activity in VEGF-mediated angiogenesis (40). Thus it is necessary to elucidate whether extracellular TGase2 participates in VEGF-induced endothelial permeability because TGase2 activation was essential for this pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that extracellular TGase2 inhibits VEGF-induced angiogenesis by impeding the interaction of VEGF with heparan sulfate proteoglycans and subsequent VEGF receptor-2 signaling independent of its transamidating activity (39). There are, however, contradictory reports on the involvement of extracellular TGase2 activity in VEGF-mediated angiogenesis (40). Thus it is necessary to elucidate whether extracellular TGase2 participates in VEGF-induced endothelial permeability because TGase2 activation was essential for this pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, extracellular TG2 promotes interactions between cells and the ECM and is important for cell spreading, migration, and differentiation (34). Moreover, the down-regulation of TG2 inhibited angiogenesis in cell culture (36). In addition, osteoblast differentiation is regulated by the presence of collagen type I in the ECM, and TGase is required for collagen secretion and extracellular deposition, which controls osteoblast differentiation (37).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of TG2 in angiogenesis is unclear and contradictory; mechanisms involving TG2 in angiogenesis are poorly understood. Indeed the enzyme can both stimulate and inhibit angiogenesis (Haroon et al, 1999;Wang et al, 2013), suggesting dependence to different contexts. For instance, in vitro studies performed in HUVEC showed that down-regulation of TG2 expression leads to inhibition of angiogenesis.…”
Section: Transglutaminase 2 In Angiogenesis and Age-related Vascular mentioning
confidence: 99%